2013
DOI: 10.3748/wjg.v19.i27.4393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of gallbladder polypoid lesions in Chinese petrochemical employees

Abstract: PLGs are not rare among Chinese petrochemical employees. Male gender, HBsAg positivity, and middle age are risk factors for developing PLGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 24 publications
3
37
1
Order By: Relevance
“…Although the reported rate of malignancy GBP is only 3–8% [ 2 ], it is a common public health issue in many countries, affecting millions of people and the prevalence is continuing to increase [ 3 ]. The prevalence of GBP is reported in the range 0.3% to 9.5% worldwide, depending on the studied population and the study design [ 4 ]. Previous studies reported that compared to western populations, Asian populations (mainly Japanese, Korean and Chinese) have a higher GBP prevalence and appear to be at a higher risk of gallbladder cancer [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reported rate of malignancy GBP is only 3–8% [ 2 ], it is a common public health issue in many countries, affecting millions of people and the prevalence is continuing to increase [ 3 ]. The prevalence of GBP is reported in the range 0.3% to 9.5% worldwide, depending on the studied population and the study design [ 4 ]. Previous studies reported that compared to western populations, Asian populations (mainly Japanese, Korean and Chinese) have a higher GBP prevalence and appear to be at a higher risk of gallbladder cancer [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GBP is reported in the range 0.3% to 9.5% worldwide, depending on the studied population and the study design [ 4 ]. Previous studies reported that compared to western populations, Asian populations (mainly Japanese, Korean and Chinese) have a higher GBP prevalence and appear to be at a higher risk of gallbladder cancer [ 4 7 ]. Recently, the prevalence of GBP is estimated from 4 to 7% in different areas of China [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such polypoid lesions have been observed in 1.4–12.3% of all GBs assessed by US, with the exact percentage depending on the population and study design. In Western countries, the prevalence of GBPs has been reported to be in the range of 1.4–6.7%, whereas in Eastern countries, mainly South Korea, Taiwan, China, and Japan, it has been reported to be 5.3–12.3% …”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, the prevalence of GBPs has been reported to be in the range of 1.4-6.7%, [1][2][3] whereas in Eastern countries, mainly South Korea, Taiwan, China, and Japan, it has been reported to be 5.3-12.3%. [4][5][6][7][8][9] Recent studies have demonstrated an association between body fat and risk of GB cancer, [10][11][12] which has a poor prognosis due to its advanced stage at diagnosis. Larger polyps, especially those larger than 1 cm, are more likely to contain foci of invasive cancer, and some studies have suggested a correlation between the presence of GBPs and the risk of GB cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PLGs are not rare in the Chinese population, most of them are benign and asymptomatic, while a small fraction of PLGs has been diagnosed as gallbladder adenocarcinoma at advanced stage. BUS is the most economical, convenient and readily available modality with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%